Dynamics and composition of breeding bird communities on Kitay Island, Central Sivash region - Valery D. Siokhin; Alex V. Matsyura (Acta Biologica Sibirica, 2025)
The Central Sivash region, a unique ecosystem of saline lakes and reed-beds, hosts important colonial waterbird communities. This study analyzes long-term changes (1949–2024) in the breeding bird population on Kitay Island, one of the area’s key islands. Our results reveal a significant ecological restructuring, marked by a pronounced increase in Great Cormorants (Phalacrocorax carbo), which became the dominant species, and a concurrent decline in Yellow-legged Gulls (Larus cachinnans). Total nest numbers peaked in the late 20th century before declining to a lower, stable level. Community analyses identified three distinct succession phases: a gull/tern-dominated assemblage (1950–1980), a cormorant-dominated phase (1990–2010), and a more mixed and diverse recent community. These shifts are interpreted in the context of environmental drivers including habitat change, interspecific competition, predation pressure, and reduced human disturbance. This most recent phase is characterized by a slight reduction in species dominance and an increase in diversity, driven by the arrival of new species. These findings demonstrate profound community turnover and highlight the dynamic response of avian populations to environmental change, providing critical insights for the conservation management of this sensitive habitat.